Contraceptive preferences among female students of the Health area at San Gregorio de Portoviejo University - Aguirre, Camila S.; Cedeño, Kendry E.; Cornejo, Anthony V.; Falcones, Aaron A.; Valera, Karen; Martínez, Ariagna; Sánchez, Rolando (Revista Gregoriana de Ciencias de la Salud, 2025)
In university students, the choice of contraceptive methods is influenced by academic, sociocultural, and economic factors. This study analyzed contraceptive preferences among health science students to identify usage patterns and access barriers, aiming to examine contraceptive preferences in female students at the Universidad San Gregorio de Portoviejo and identify the factors influencing their choices. It was a descriptive, non-experimental, cross-sectional study involving 85 students from Medicine, Dentistry, Nursing, Nutrition, and Integral Aesthetics programs. A digital survey with single-choice and multiple-choice questions was administered. The male condom was the most commonly used method, followed by oral contraceptives. Pharmacies were the primary source of acquisition, and most participants received information from general practitioners. Therefore, it is recommended to strengthen sexual education and improve access to information to optimize decision-making in reproductive health.